Investigating the effect of fabrication method on the stability and acoustic response of microbubble agents - Mohamedi, G; Hosny, N; Rademeyer, P; Park, Y; Owen, J; Pham, T; Wong, J; Kuimova, M; Stride, E (2013)
Microbubbles stabilized by a surfactant or polymer coating are already in clinical use as ultrasound imaging contrast agents. They have also been widely investigated as vehicles for drug delivery and gene therapy that can be tracked and triggered using ultrasound. Extensive studies have been made of the effects of the coating material and gas core on microbubble characteristics but the influence of the fabrication method has received less attention. The aim of this study was to compare the behavior of microbubbles prepared using different techniques. Phospholipid-coated microbubbles were produced using sonication, electrospraying or in a specially designed microfluidic device. The microbubbles were observed using optical, electron and fluorescence lifetime imaging microscopy (FLIM) to interrogate their surface microstructure and stability over time. Their acoustic response was then determined in a flow chamber by detecting the pressure scattered from individual microbubbles as they passed trough the focal region of a transducer (centre frequencies 1, 2.25 and 3.5 MHz; peak negative pressures 50-300kPa). The method of bubble generation was found to significantly affect the bubble surface characteristics, stability and acoustic response. The results demonstrate that the processing method affects not only the bubble size distribution but other characteristics important for biomedical applications. © 2013 Acoustical Society of America.